Induction of Senescence in Head and Neck Tumor Cells by Combination of Irradiation and DNA Repair Inhibitors - Dobler, Clara; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Senescence Induction by Combined Ionizing Radiation and DNA Damage Response Inhibitors in Head and Neck Squamous Cell Carcinoma Cells - Dobler, Clara; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Cells, 2020)
DNA damage response inhibitors (DDRi) may selectively enhance the inactivation of tumor cells in combination with ionizing radiation (IR). The induction of senescence may be the key mechanism of tumor cell inactivation in this combinatorial treatment. In the current study the effect of combined IR with DDRi on the induction of senescence was studied in head and neck squamous cell carcinoma (HNSCC) cells with different human papilloma virus (HPV) status. The integrity of homologous recombination (HR) was assessed in two HPV positive, two HPV negative HNSCC, and two healthy fibroblast cell cultures. Cells were treated with the DDRi CC-115 (DNA-dependent protein kinase, DNA-pK; dual mammalian target of rapamycin, mTor), VE-822 (ATR; ataxia telangiectasia and Rad3-related kinase), and AZD0156 (ATM; ataxia telangiectasia mutated kinase) combined with IR. Effects on senescence, apoptosis, necrosis, and cell cycle were analyzed by flow cytometry. The fibroblast cell lines generally tolerated IR or combined treatment better than the tumor cell lines. The ATM and ATR inhibitors were effectively inducing senescence when combined with IR. The DNA-PK inhibitor was not an important inductor of senescence. HPV status and HR activity had a limited influence on the efficacy of DDRi. Induction of senescence and necrosis varied individually among the cell lines due to molecular heterogeneity and the involvement of DNA damage response pathways in senescence induction.
CRIS-Team Scopus Importer:2020-10-30
Keywords: ATM; ATR; DNA damage response inhibitor; DNAPK; HNSCC; homologous recombination; ionizing radiation; kinase inhibitor; radiosensitivity; senescence